Microvascular tissue transfer in reconstruction of anterior skull base defects secondary to sinonasal malignancies: a case series and proposed reconstructive framework - Nikhil Prasad; Kripa Shankar Mishra; Rajan Arora; Anchit Kumar; Samarth Gupta; Sourav Sarkar (Egyptian Journal of Neurosurgery)
Abstract Sinonasal malignancies such as lymphoepithelial carcinoma (LEC) and esthesioneuroblastoma (ENB) are rare but aggressive neoplasms that frequently necessitate extensive resection of anterior skull base structures, creating complex defects. This case series discusses two patients with recurrent sinonasal malignancies who underwent anterior skull base reconstruction using microvascular free flaps. The first case involved a recurrent LEC managed with a radial forearm free flap, and the second case involved a recurrent ENB with cerebrospinal fluid (CSF) leaks managed via an anterolateral thigh free flap. Both cases highlight the role of free flap reconstruction in managing large, high-risk defects while addressing complications such as CSF leaks, infections, and prior radiation-induced tissue damage. This paper underscores a reconstructive algorithm for managing extensive anterior skull base defects using microvascular free tissue transfer.